Islam Melayu dan Islam Jawa: Studi Komparatif Akulturasi Islam dan Kebudayaan dalam Perspektif Sejarah - Yusril Fahmi Adam; Elza Ramona; Imam Muhsin (IAIN Ponorogo, 2023)
Malay Islam and Javanese Islam are two forms of practice and expression of religion (Islam) in two different regions, and each is unique, so it is not uncommon for one to be opposed to the other. This study aims to analyze differences in Islamic and cultural acculturation in the two regions from a historical perspective. In its analysis, this study uses historical methods with an anthropological approach and cultural diffusion theory. The findings in this study are that there are differences in the acculturation of Islam and culture in Malay and Java in terms of process and outcome. In terms of process, the acculturation of Islam and culture in Malay occurs in an integrative-structural manner, while in Java it occurs in a dialogical-cultural way. In the Malay region, the process of acculturation occurs as a whole through the socio-political system and the legitimacy of power, while in Java, there is a process of dialogue in order to achieve harmony with the local culture. The process then produces a different form of Islamic practice. The conclusion in this study is that in Malay the form of Islamic community practice is more formalistic in nature, while in Java it is more substantive, so this makes the element of novelty in this study.Â AbstrakIslam Melayu dan Islam Jawa adalah dua wujud praktik dan ekspresi beragama (Islam) masyarakat pada dua wilayah yang berbeda dan masing-masing memiliki keunikan, sehingga tidak jarang antara satu dengan lainnya dipertentangkan. Studi ini bertujuan untuk menganalisis perbedaan akulturasi Islam dan kebudayaan pada dua wilayah tersebut dari perspektif historis. Dalam analisisnya, penelitian ini menggunakan metode sejarah dengan pendekatan antropologi dan teori difusi budaya. Temuan dalam penelitian ini adalah akulturasi Islam dan kebudayaan di Melayu dan Jawa terdapat perbedaan pada segi proses dan hasilnya. Dari segi proses, akulturasi Islam dan kebudayaan di Melayu terjadi secara integratif-struktural, sedangkan di Jawa terjadi secara dialogis-kultural. Di wilayah Melayu proses akulturasi terjadi secara menyeluruh melalui sistem sosial-politik dan legitimasi kekuasaan, sedangkan di Jawa terjadi proses dialog guna mencapai harmoni dengan kebudayaan setempat. Proses tersebut kemudian menghasilkan wujud praktik keislaman yang berbeda pula. Kesimpulan dalam penelitian ini adalah jika di Melayu wujud praktik keislaman masyarakat lebih bersifat formalistik, sedangkan di Jawa lebih bersifat substantif, sehingga hal ini yang menjadikan unsur kebaruan di dalam penelitian ini